MMP25 Regulates Immune Infiltration Level and Survival Outcome in Head and Neck Cancer Patients - Liang, Yujie; Guan, Chenyu; Li, Kan; Zheng, Guangsen; Wang, Tao; Zhang, Sien; Liao, Guiqing (Frontiers in Oncology, 2020)
Background: MMP25 is a critical gene of matrix metalloproteinases. However, the role of MMP25 to molecular mechanism, immune infiltration level, and prognosis in head and neck cancer remain unclear. Methods: MMP25 expression was analyzed by the TCGA database. The influence of MMP25 on clinical prognosis using Kaplan-Meier analysis and COX regression analysis. The correlations between MMP25 and cancer immune infiltration level was investigated by CIBERSORT, TIMER and ESTIMATE. In addition, correlations between MMP25 expression and downstream molecular regulation were analyzed by GSEA, edgeR and WGCNA. Results: MMP25 is correlated with prognosis and immune infiltrating levels, especially activated CD4+ memory T cells, in head and neck cancer. Moreover, MMP25 expression potentially contributes to regulation of genes, such asIRF8, IKZF1, and DOCK2, and tumor associated pathways, including p53 signaling pathway, PI3K/AKT/mTOR signaling pathway and JAK/STAT signaling pathway. Conclusions: These findings suggest that MMP25 play a critical role in the prognosis and immune infiltration level of head and neck cancer. In addition, MMP25 expression was significantly correlated with the regulation of various oncogenes and tumor related pathways.